2011
DOI: 10.1519/jsc.0b013e3181ddf6db
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Effect of Acute Caffeine Ingestion on Intense Resistance Training Performance

Abstract: The primary aim of the study was to determine the efficacy of acute caffeine intake to enhance intense resistance training performance. Fourteen resistance-trained men (age and body mass = 23.1 ± 1.1 years and 83.4 ± 13.2 kg, respectively) who regularly consumed caffeine ingested caffeine (6 mg · kg(-1)) or placebo 1 hour before completion of 4 sets of barbell bench press, leg press, bilateral row, and barbell shoulder press to fatigue at 70-80% 1-repetition maximum. Two minutes of rest was allotted between se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
2
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 38 publications
1
51
2
5
Order By: Relevance
“…Spriet (2014) found that moderate to high caffeine doses (5-13 mg/kg) ingested 1h before and during exercise increase endurance exercise performance in laboratory and sport field settings. In a follow-up, Astorino et al (2011a) gave 6 mg/kg caffeine 60 min before exercise (completion of four sets of barbell bench press, leg press, and bilateral row) to resistant trained men who were regular caffeine consumers, showing a significant effect of acute caffeine ingestion on leg press performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spriet (2014) found that moderate to high caffeine doses (5-13 mg/kg) ingested 1h before and during exercise increase endurance exercise performance in laboratory and sport field settings. In a follow-up, Astorino et al (2011a) gave 6 mg/kg caffeine 60 min before exercise (completion of four sets of barbell bench press, leg press, and bilateral row) to resistant trained men who were regular caffeine consumers, showing a significant effect of acute caffeine ingestion on leg press performance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Warren et al (2010) demonstrated that caffeine ingestion (1-9 mg/kg) improves maximal voluntary contraction strength and muscular endurance. Astorino et al (2011a) reported that caffeine consumption (6 mg/kg) before exercise (60 min) has significant effect on leg press performance. However, in another study, it was shown that ingestion of caffeine has no effect on 1RM strength and muscular endurance (Astorino, Rohmann, Firth, 2008;Beck et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the effects of caffeine on muscular endurance performance using a variety of protocols [12][13][14][15][16][17][18][19][20][21][22][23]26,[39][40][41] (Table 1). Caffeine's ability to increase the amount of repetitions performed at set percentages of participants 1 RM is an area that has been relatively well explored [13][14][15][16][17][18][19][20][21][22][23]26,39,40].…”
Section: Caffeine and Muscular Endurancementioning
confidence: 99%
“…Caffeine's ability to increase the amount of repetitions performed at set percentages of participants 1 RM is an area that has been relatively well explored [13][14][15][16][17][18][19][20][21][22][23]26,39,40]. In 2011, Astorino et al [40] recruited fourteen resistance trained, average caffeine (~218 mg/day) consuming males to perform resistance exercises to failure. Participants consumed either caffeine (6 mg.kg.bw -1…”
Section: Caffeine and Muscular Endurancementioning
confidence: 99%